(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Migraine is a chronic primary headache disorder with episodic attacks which affects the people in the most productive periods of their working lives; women are affected up to four times more often than men. Objective: The purpose of the present study was to identify the association of migraine and risk of ischemic stroke in young women. Methodology: It’s a hospital based case-control study carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University from January 2010 to December, 2012. Results: The result obtained from our study shows that migraine and ischemic stroke were strongly associated; 60% (95% confidence interval 48% to 71%) of cases had migraine compared with 30%(23% to 37%) of controls (P < 000 1). This association persisted after we controlled for age, history of hypertension, use of oral contraceptives, and smoking.Women with migraine had a more than threefold increased risk of ischemic stroke compared with women without migraine. This increase occurred with both types of migraine, although the risk was higher with migraine with aura (odds ratio 6-2) than with migraine without aura. Conclusion: In conclusion, the risk of ischemic stroke was higher among young women with migraine who smoked or who took oral contraceptives. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):193-197